2016
DOI: 10.1002/srin.201600150
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fine Grained Dual Phase Steel on Bake Hardening Properties

Abstract: High strength dual phase (DP) steels have been increasingly used in car body structure for reducing weight and increasing safety performance. Bake hardening process is widely applied for improving final mechanical properties of formed components by means of carbide precipitation and occurred Cottrell cloud. In this work, effects of bake hardening on mechanical behavior of coarse and fine grain DP steels are investigated. Initially, fine grain ferritic-pearlitic structure is produced from a low carbon steel by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Different techniques have been used for grain refinement of DP steels. The intercritical annealing of cold‐worked martensite or ultrafine grained (UFG) ferrite‐carbide aggregate, fast and ultrafast heating, ultrafast cooling (UFC), Deformation‐induced ferrite transformation (DIFT), and severe plastic deformation have been recently practiced. Most of these techniques are based on prior deformation and need rolling facilities or more complicated and expensive deformation routes.…”
Section: Introductionmentioning
confidence: 99%
“…Different techniques have been used for grain refinement of DP steels. The intercritical annealing of cold‐worked martensite or ultrafine grained (UFG) ferrite‐carbide aggregate, fast and ultrafast heating, ultrafast cooling (UFC), Deformation‐induced ferrite transformation (DIFT), and severe plastic deformation have been recently practiced. Most of these techniques are based on prior deformation and need rolling facilities or more complicated and expensive deformation routes.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Cai et al, Das et al, Ahmad et al, Kalhor and Mirzadeh, Seyedrezai et al, and Schemmann et al showed that changing the initial microstructure can significantly affect the attributes of the DP microstructure. Moreover, the effect of tempering has also been noted . On another front, Calcagnotto et al and Papa Rao et al focused on warm deformation and intercritical annealing, where the importance of bimodal ferrite grain structure was also discussed .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the effect of tempering has also been noted. [17][18][19] On another front, Calcagnotto et al [20] and Papa Rao et al [21] focused on warm deformation and intercritical annealing, where the importance of bimodal ferrite grain structure was also discussed. [11] Azizi-Alizamini et al [22] studied the effects of cold rolling of tempered martensite, subsequent tempering step, and heating rate to intercritical annealing temperature.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, severe plastic deformation (SPD) in combination with intercritical annealing has been a particular technique in the category of thermomechanical processing which could be employed to produce UFG DP steels, as shown in previous studies. [ 27–31 ] Among all variously available SPD techniques, [ 32,33 ] constrained groove pressing (CGP) has become one of the effective methods for generating severe plastic deformation on sheet metals, in which the initial dimensions of sample were not altered. During the CGP process, the workpiece was subjected to a repetitive corrugating and straightening under the plane strain deformation condition by using alternate pressing with the asymmetrically grooved and flat dies.…”
Section: Introductionmentioning
confidence: 99%